Macro-Financial Implications of Corporate (De)Leveraging in the Euro Area Periphery - Goretti, Manuela (IMF Working Papers; Working Paper ;, 2013)
High corporate indebtedness can pose an important threat to the adjustment processes in some of the Euro area periphery countries, through its drag on investment as well as the possible migration of private sector losses to the sovereign balance sheet. This paper examines the macroeconomic implications of corporate debt overhang in recent years, confirming empirical evidence in the literature on the relationship between a firm's balance sheet position and its investment choices, especially beyond certain threshold levels. Building on an event study of past crisis experiences with corporate deleveraging, it also discusses the expected macro-financial impact of the ongoing deleveraging processes in these countries, presenting available policy options to facilitate an orderly balance-sheet adjustment and support a return to productivity and growth.